SELEKSI INDUK KAMBING PERANAKAN ETAWAH BERDASARKAN NILAI ESTIMATED REAL PRODUCINGABILITY BOBOT SAPIH DI KELOMPOK TANI MARGARINI - Ariestama, Dani; Hamdani, M.Dima Iqbal; Harris, Idalina (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Estimated Real Producing Ability (ERPA) value are maximally estimated of the ability of mother doe, which is allegedly based onexisting perfomans. Producing ability for production capability of an animal which is closelyrelated with the value of Repeatability, the average production, many production records, and the averageproduction within a population. Calculations of ERPA are entering information such asthe average mother inkidbirth production which compared with the average of herdmate production. Herdmate are all parents within thesame farm, who had kidbirth in the same relative time, but not the half? brother of a father.The research was conducted on May 2013 until June 2013 in Sungai Langka village, Subdistrict Gedong Tataan,Pesawaran District. This research using a survey method by analyzing production records the birth of the first andsecond of the 30 samples of doe Etawah crossbreed. Analysis was performed by searching for weaning weightcorrected, the estimated value Repeatability and the value of ERPA weaning weight in Margarini farmer groupsgoat.The result said that the average of corection weaning weight PE goat is 19,48±1,47 kg. The value of repeatabilityweaning weight PE Goat gotten in the research is 0,57 and the average of value ERPA weaning weight PE goat is19,84±1,067 kg. Base on the result of research known 20 of 30 goat (66,6 %) mother doe PE has ERPA above ofaverage.